Ecology of social administration in India - Barik, R.K. (1994)
The welfare state is a modern creation which in theory takes care of the OCD, the young, the unemployed and various categories of destruction. The Indian state is a welfare state which guarantees equal opportunities to all its citizens. But these ideals have not been translated into practice due to various obstacles.- Reproduced
Keywords: Ecology - India; Welfare state - India; Social welfare - India; Social welfare